Evidence-informed massage therapy – an Australian practitioner perspective. (May 2018) - Ooi, Soo Liang; Smith, Lauren; Pak, Sok Cheon
Abstract: Massage therapy (MT) is the most popular complementary and alternative medicine therapy used by the Australian public. With the growing emphasis by the Australian health authority on evidence-informed healthcare decision-making, there is an increasing demand for massage therapists to move towards the evidence-informed practice (EIP). With MT research gaining significant attention over the last 30 years, clinical evidence exists to support the efficacies of MT on many health conditions, including chronic low back pain. This growing body of research supports MT to become an evidence-informed therapeutic modality. The evidence utilization process of asking clinical questions, searching for available research evidence, and appraising the evidence critically can be incorporated into the clinical practice of MT. Moreover, integrating practitioners' skills and experience with research evidence enables the best treatment plan to address the clients' needs and stated goals. No dichotomy exists between scientific research and the humanistic client care of MT. A massage therapist can gain greater confidence in practice, improve critical thinking and decision-making skills, and increase career satisfaction through EIP. Despite its high public utilization, massage therapists in Australia remain a low-paying profession dominated by part-time workers who rarely utilize research evidence in practice. Professional associations of massage therapists in Australia need to play a key role in promoting EIP through continuing professional education, providing the access to research information and resources, as well as fostering a culture of EIP. Highlights: Massage therapy (MT) is the most popular complementary and alternative medicine therapy used by the Australian public. There is an increasing demand for massage therapists to move towards the evidence-informed practice (EIP). The growing body of research supports MT to become an evidence-informed therapeutic modality. Massage therapists in Australia rarely utilize research evidence in practice. Professional associations of massage therapists in Australia need to play a key role in promoting EIP through continuing professional education.